2020
DOI: 10.1186/s13014-020-01516-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CTVHR and organs at risk contours between TRUS and MR images in IB cervical cancers: a proof of concept study

Abstract: Purpose: To compare CTV HR and OAR dimensions and inter-rater agreement between magnetic resonance (MR) and trans-rectal ultrasound (TRUS) images in IB cervical cancer patients. Methods: IB cervical cancer patients treated with (chemo)radiotherapy plus MR-guided brachytherapy (BT) were prospectively enrolled in this study. Radiation oncologists contoured CTV HR and OARs in pre-BT MR images (MRI) and intra-operative TRUS images. These contours were subsequently compared in regard to volume and dimension. Contou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Several groups have recently investigated the use of US for applicator reconstruction and/or contouring using either transrectal [2][3][4][5] or transabdominal 6 US in GYN brachytherapy. Common issues with these methods are shadowing beyond inserted applicators, 3,4 limited field of view/depth of imaging, [2][3][4] and deformation of the target and/or OAR volumes due to the presence of ultrasound probes. [2][3][4] One way to overcome these issues is to utilize both US with CT, [4][5][6] where US provides the soft tissue contrast of the vaginal wall and the CT image provides visualization of the applicator and OARs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have recently investigated the use of US for applicator reconstruction and/or contouring using either transrectal [2][3][4][5] or transabdominal 6 US in GYN brachytherapy. Common issues with these methods are shadowing beyond inserted applicators, 3,4 limited field of view/depth of imaging, [2][3][4] and deformation of the target and/or OAR volumes due to the presence of ultrasound probes. [2][3][4] One way to overcome these issues is to utilize both US with CT, [4][5][6] where US provides the soft tissue contrast of the vaginal wall and the CT image provides visualization of the applicator and OARs.…”
Section: Introductionmentioning
confidence: 99%
“…TVUS may eliminate the need for CT-based treatment planning, which enables a streamlined intraoperative workflow that is typically associated with decreased procedure time and less patient motion. 2 To successfully use the 3D TVUS system as the primary image modality for the treatment planning pro-cess, commissioning tests must be performed to ensure the technical specifications of the system's performance are on par with the CT-based treatment planning process it is intended to replace. This study outlines the technical commissioning steps that are required to utilize the 3D TVUS system for GYN HDRBT treatments with the MCVC using 3D TVUS for applicator reconstruction as a replacement of CT.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups have investigated threedimensional transrectal ultrasound (3DTRUS) in delineation of the high-risk clinical target volume and organs at risk in intracavitary GYN HDRBT (11e13). Common issues with 3DTRUS were difficulty imaging beyond the applicator (11,12) and reduced high-risk clinical target volume thickness (11,13) in part because of the transrectal ultrasound probe compressing the cervix anteriorly. Rodgers et al (14) used 3DTRUS to intraoperatively guide IS needle implants but also experienced issues with imaging beyond the vaginal cylinder, thus making it difficult to image IS needles behind the vaginal cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…9 The incorporation of 3D US imaging intraoperatively has the potential to reduce the number of poor-quality implants, including perforations, which may still occur under 2D guidance. 9,13 Both 2D [24][25][26][27][28][29][30][31] and 3D 15,[32][33][34][35][36] US have been explored in intracavitary brachytherapy (ICBT) [24][25][26][27]32,36 and interstitial brachytherapy (ISBT) [28][29][30][31]33,34 treatments of gynecologic malignancies. Transabdominal ultrasound (TAUS) is routinely used to verify intrauterine tandem placements 25 and has been investigated for image-based treatment planning, demonstrating its efficacy for this purpose.…”
mentioning
confidence: 99%
“…Transrectal ultrasound (TRUS) has also been explored for both guidance of applicator placement [28][29][30][31]33 and delineation of targets and OARs. 13,15,32,35 Nesvacil et al 36 investigated the combination of 3D TRUS and CT images for 3D IGABT of a cervical tumor in a proof -of -concept patient using a tandem-and-ring applicator. The study found that this approach was feasible, producing treatment plans clinically comparable with those created on MR images; however, the authors observed limitations related to the restricted US field-of -view, preventing complete visualization of OARs and the applicator, particularly the tandem tip.…”
mentioning
confidence: 99%